2017
DOI: 10.1371/journal.pcbi.1005585
|View full text |Cite
|
Sign up to set email alerts
|

Independent regulation of gene expression level and noise by histone modifications

Abstract: The inherent stochasticity generates substantial gene expression variation among isogenic cells under identical conditions, which is frequently referred to as gene expression noise or cell-to-cell expression variability. Similar to (average) expression level, expression noise is also subject to natural selection. Yet it has been observed that noise is negatively correlated with expression level, which manifests as a potential constraint for simultaneous optimization of both. Here, we studied expression noise i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 67 publications
(184 reference statements)
7
65
3
Order By: Relevance
“…Consistent with this, the TATA box promoter element is positively correlated with both gene expression plasticity and cell-to-cell expression noise (4,44). Recent studies have also identified certain types of histone modification as significantly associated with expression noise (44,45), some of which were independently identified here to regulate expression plasticity. However, closer examination of the relationship between noise and plasticity demonstrates that the coupling between the two is highly conditional and evolvable in both yeast (4) and E. coli (46).…”
Section: Independent Regulation Of Gene Expression Level Plasticitysupporting
confidence: 77%
See 2 more Smart Citations
“…Consistent with this, the TATA box promoter element is positively correlated with both gene expression plasticity and cell-to-cell expression noise (4,44). Recent studies have also identified certain types of histone modification as significantly associated with expression noise (44,45), some of which were independently identified here to regulate expression plasticity. However, closer examination of the relationship between noise and plasticity demonstrates that the coupling between the two is highly conditional and evolvable in both yeast (4) and E. coli (46).…”
Section: Independent Regulation Of Gene Expression Level Plasticitysupporting
confidence: 77%
“…Furthermore, while H3K27me3, H3K4me1, and H3K9ac are associated with high expression noise in mouse embryonic stem cells (44), we found that these modifications do not affect expression plasticity. Interestingly, H3K36me3, H3K79me2, and H4K20me1 have been independently identified as significantly associated with restricted expression noise (45) and plasticity (Figure 6).…”
Section: Independent Regulation Of Gene Expression Level Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Both gene expression noise and parametric variations are common in biological systems 1,4,6,7,13,22,48 . On the one hand, the Gillespie algorithm (Fig S2) has been used to model the stochastic dynamics of gene expression caused by low copy number and slow switches between gene states 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Noise or stochastic fluctuations in molecular components have been shown to play important role in many biological processes [1][2][3] , such as phenotypic switching, gene expression coordination, cell cycle and cell differentiation 4 , in both prokaryotic 5 and eukaryotic organisms 3,4,6,7 . Noise can propagate in a gene network with a cascade of circuit motifs, and the expression level of a gene can vary up to six orders of magnitude between cells 1,8 .…”
Section: Introductionmentioning
confidence: 99%